Ranking and quality of universities: What makes US universities to be at the top? - Elise S. Brezis (Bar-Ilan University, Department of Economics, 2011)
The purpose of this study is to isolate the factors influencing universities' quality. An interesting fact is that of the ten top-rated US universities, nine are private. Therefore, previous studies have claimed that there is a correlation between universities being private and their quality. The purpose of this paper is to analyze whether private universities are indeed of higher quality. The analysis presented herein is based on data collected on 508 universities in 40 countries. I show that flexibility in governance is the important element affecting quality, and not being private per se.
Keywords: 330; Hochschule; Vergleich; Teilstaat; USA